2015
DOI: 10.1016/j.cortex.2015.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical substrates and neurocognitive predictors of daily numerical abilities in mild cognitive impairment

Abstract: Patients with mild cognitive impairment experience difficulties in mathematics that affect their functioning in the activities of everyday life. What are the associated anatomical brain changes and the cognitive correlates underlying such deficits? In the present study, 33 patients with Mild Cognitive Impairments (MCI) and 29 cognitively normal controls underwent volumetric MRI, and completed the standardized battery of Numerical Activities of Daily Living (NADL) along with a comprehensive clinical neuropsycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…It has been reported that social isolation induces stress and depressive-like behavior in humans and animals (Fone KC & Porkess MV, 2008). Four weeks of social isolation induced depressive-like behavior in C57BL/6J mice (Koike H et al, 2009;Dang YH et al, 2015;) and ICR mice (Benavides-Varela S et al, 2015). These reports are consistent with our findings that BALB/c mice showed depressive-like behavior after 4 weeks of social isolation.…”
Section: Social Isolation Induced Depressive-like Behaviorsupporting
confidence: 93%
“…It has been reported that social isolation induces stress and depressive-like behavior in humans and animals (Fone KC & Porkess MV, 2008). Four weeks of social isolation induced depressive-like behavior in C57BL/6J mice (Koike H et al, 2009;Dang YH et al, 2015;) and ICR mice (Benavides-Varela S et al, 2015). These reports are consistent with our findings that BALB/c mice showed depressive-like behavior after 4 weeks of social isolation.…”
Section: Social Isolation Induced Depressive-like Behaviorsupporting
confidence: 93%
“…The atrophy and disrupted white matter integrity of SFG was proposed to be a marker of disease severity and impending cognitive decline in late-life depression (Reppermund et al, 2014 ; Boccia et al, 2015 ). Furthermore, the volumetric alteration in SFG was correlated with numerical daily function, including working memory and abstract reasoning (Benavides-Varela et al, 2015 ). Our previous work also demonstrated that the abnormal intrinsic activity in SFG was related to cognitive dysfunction in LOD (Yue et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…A number of recent investigations lead to divergent conclusions, in part depending on which numerical functions were measured. In the elderly, even in healthy ones, a certain degree of impairment of arithmetical functions can be found (Duverne and Lemaire, 2004 ; El Yagoubi et al, 2005 ; Lemaire and Arnaud, 2008 ; Benavides-Varela et al, 2015 ), which is often clinically hard to distinguish from that produced by neurological deterioration (Zamarian et al, 2007a , b ). However, not all studies show an age-related decline.…”
Section: Introductionmentioning
confidence: 99%